Coastal Area Management Based on Disaster Mitigation: A Case Study in Purworejo Regency, Indonesia - Hidajat, Wahju Krisna; Anggoro, Sutrisno; Najib, Najib (Geological Agency, 2021)
DOI:10.17014/ijog.8.2.147-156Indonesia is an archipelago blessed with the wealth of coastal resources, but also with the risk of natural hazards including tectonic earthquake and tsunami. This potential risk is high in the Purwodadi Subregency, Purworejo Regency, Indonesia, because of its location in an active subduction zone at the edge of the Indian Ocean. Therefore, this study was conducted in the region located on the southern coast of Java Island. The high probability of disaster in the area needs a proper coastal management strategy and mitigation measures. Hence, this study aims to establish an appropriate policy using the strength-weakness-opportunity-threat (SWOT) analysis. Furthermore, the data obtained from this novel analysis include the population and social vulnerability, geological conditions, landuse allocation, and disaster strategies. Each is carefully assessed and then incorporated into the matrix to obtain the result. In addition, the alternative strategies used are the development of disaster mitigation facilities, infrastructure, and institutional strengthening.